Teaching content and language in the multilingual classroom international research on policy, perspectives, preparation and practice - Hammer, Svenja; Viesca, Kara Mitchell; Commins, Nancy L. (Routledge Research in Language Education, 2020)
This book brings together research from six different countries across three continents where teacher educators and policy makers are addressing the under-preparation of content teachers to work effectively with multilingual learners. By highlighting this relatively young field of research at an international level, the book advances the research-based knowledge of the field and promotes international research relationships and partnerships to better support the education of multilingual learners and their teachers. The chapters represent high-quality empirical qualitative, quantitative, and mixed methods studies about pre-service and in-service teachers. Comprising four sections, each represents a critical aspect of the equitable teaching of multilingual learners. All the research was conducted in countries that belong to OECD (Organisation for Economic Co-operation and Development) and the PISA (Programme for International Student Assessment) enabling the reader to compare contexts and outcomes. This book will be of particular interest to academics, researchers, and post-graduate students in the fields of language education, teacher education, and education for multilingual learners. It will be of great value to anyone concerned with equity and social justice for multilingual learners whose languages, cultural practices, and resources are often overlooked and/or marginalized in the schools they attend